2004
DOI: 10.2307/40252702
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing Work-Family Policies for Faculty

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Institutional commitment can shape the availability and usage of policies. Similarly, department chairs play a critical role in faculty members' success in balancing work and family responsibilities (Drago et al 2005;Quinn et al 2004;Sullivan et al 2004;Waltman and August 2005). Institutional and departmental leaders can help create a climate in which balancing work and family is valued.…”
Section: Involving Fathersmentioning
confidence: 97%
See 1 more Smart Citation
“…Institutional commitment can shape the availability and usage of policies. Similarly, department chairs play a critical role in faculty members' success in balancing work and family responsibilities (Drago et al 2005;Quinn et al 2004;Sullivan et al 2004;Waltman and August 2005). Institutional and departmental leaders can help create a climate in which balancing work and family is valued.…”
Section: Involving Fathersmentioning
confidence: 97%
“…Given today's institutional climate, many faculty members are unwilling to take leave for fear of suffering damage to their careers (Finkel et al 1994;Sullivan et al 2004;Yoest 2004). In a survey of faculty at an American research university, Finkel et al (1994) found that, while the majority of faculty members supported paid leave for female faculty for childbirth and stopping the tenure clock, they believed that taking such a leave would hurt them professionally.…”
Section: Balancing Personal and Professional Livesmentioning
confidence: 98%
“…Results of this descriptive study may guide UCD and other universities to adapt the policies and their implementation to improve faculty satisfaction and career development in these disciplines. 23 …”
mentioning
confidence: 99%
“…Hewlett (2002) advocated part-time tracks for careers in general; moreover, Hill, Märtinson, Ferris, and Baker (2004) found that among professional women with pre-schoolers, those with highstatus, career-oriented positions with pro-rated pay and benefits reported more workfamily balance and no less perceived career opportunity than their full-time counterparts. Evaluating department chairs and academic deans according to their active commitment to and execution of family-friendly policies and their cultivation of a family-friendly culture is necessary (Sullivan, Hollenshead, & Smith, 2004). Indeed, work-family practices are ''essential for women professors to participate on an equal basis with their male colleagues in higher education'' (American Association of University Professors, 2001, p. 61).…”
Section: Resultsmentioning
confidence: 97%